PENGEMBANGAN TURBIN ANGIN SUMBU VERTIKAL TIPE TRIPLE-STAGE SAVONIUS DENGAN POROS GANDA - Chamdani Irwan Saputra; Cecep E. Rustana; Hadi Nasbey (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research is the development of vertical axis wind turbines savonius type of triple stage with double shaft. This type of turbine is a vertical turbine that utilizes the drag force and can rotate at low wind speeds. This turbine uses pulley and belt transmission system. The aim of this study is expected to increase the efficiency of the resulting value of vertical axis wind turbines of type triple - stage savonious. The turbine is designed to make six rotor with three rotor of each shaft. Materials for rotor using the pipe pvc with dimensions of each rotor diameter of 20 cm and a height of each rotor is 19 cm. The research method used was experimental , with direct measurements using a laboratory scale wind tunnel device as the source of the wind. From the test results of rotor arrangement with angel 0 o , this turbine is able to produce a power output of 0.239 watt with efficiency at 2.17%. Keywords: wind, savonius turbine, pulley, belt, double shaft, efficiency.